The Influence of Variations in Shape and Placement Sliding Walls on The Behavior of Multi-Story Building Structures to Withstand Earthquake Loads (Case Study: Building Pasar Raya Inpres Block) - Apriwan, Anggi; Zola, Prima (Universitas Negeri Padang, 2024)
System the structure of Building a Pasar Raya Inpres Padang Block IV, namely system double that uses wall shift as retainer lateral load and SRPMK as retainer style gravity, but cold sliding on the building the only there is on the 1st floor only if wall shifts No continuously until building roof floor so can influence behavior structure building the like mark style shift basis, displacement, deviation between the floor and p-delta influence. The study this aims to compare mark style shift basis, displacement, and deviation between which floor and p-delta later will compared against 4 variation models shape and placement wall shift. The method used that is method comparative with analysis uses response spectrum using ETABS software. Results of the study show model 2 structure has a mark base shear namely 3658,658 kN. Model 2 has a mark displacement the smallest in the x direction is 3,766 mm and Model 4 has a mark displacement the smallest in the y direction is 2,347 mm. Model 2 has a mark deviation atar floor smallest namely 8,019 mm for the X direction and 4,015 for the Y direction. All models are confirmed safe at the moment checking the P-Delta effect, with model 2 having the mark lowest for the X direction and Y direction.